Pharmacological vs Exercise Stress Echocardiography for Detection of Cardiac Allograft Vasculopathy - Gebska, Milena A. (Mayo Clin Proc Innov Qual Outcomes, 2020)
OBJECTIVE: To test the hypothesis that exercise and dobutamine would provide levels of cardiac stress that are comparable to those achieved in a general stress test population, and to one another, in heart transplant recipients. PATIENTS AND METHODS: From February 10, 2015, to December 31, 2017, 81 patients underwent exercise stress (N=45) or dobutamine stress (N=36) echocardiography at a mean ± SD of 11±14 years (range, 1-29 years) after heart transplant. Hemodynamic and inotropic responses were compared between groups, and to a prior test, longitudinally. The primary outcome was peak heart rate (HR) × systolic blood pressure (SBP). RESULTS: Peak exercise HR × SBP × 10(−3) was a mean ± SD of 24.9±4.9 mm Hg/min for exercise stress vs 21.2±3.4 mm Hg/min during dobutamine stress (P<.001). In 35 patients who underwent a dobutamine stress test followed later by another dobutamine stress test, peak HR × SBP changed by 4.2%±16% (P=.05). In 25 patients who underwent a dobutamine stress test followed later by an exercise stress test, peak HR × SBP increased by 12%±23% (P=.002 vs serial dobutamine stress tests). Peak exercise HR did not correlate with time since heart transplant, patient age, or graft age. Peak dobutamine HR correlated modestly with patient age (r(2)=0.28). Inotropic responses were similar in both groups. Overall, patients preferred exercise stress testing to dobutamine stress tests. Dobutamine stress testing was more expensive than exercise stress tests. CONCLUSION: Exercise induces a level of cardiac stress that is equal to or greater than dobutamine-induced stress, at lower cost, in heart transplant recipients who express preference for exercise stress testing.